New Insights and Methods for Recording and Imaging Spontaneous Spreading Depolarizations and Seizure-Like Events in Mouse Hippocampal Slices - Lu, Yi-Ling; Scharfman, Helen E. (Frontiers in Cellular Neuroscience, 2021)
Spreading depolarization (SD) is a sudden, large, and synchronous depolarization of principal cells which also involves interneurons and astrocytes. It is followed by depression of neuronal activity, and it slowly propagates across brain regions like cortex or hippocampus. SD is considered to be mechanistically relevant to migraine, epilepsy, and traumatic brain injury (TBI), but there are many questions about its basic neurophysiology and spread. Research into SD in hippocampus using slices is often used to gain insight and SD is usually triggered by a focal stimulus with or without an altered extracellular buffer. Here we optimize an in vitro experimental model allowing us to record SD without focal stimulation, which we call spontaneous. This method uses only an altered extracellular buffer containing 0 mM Mg2+ and 5 mM K+ and makes it possible for simultaneous patch and extracellular recording in a submerged chamber plus intrinsic optical imaging in slices of either sex. We also add methods for quantification and show the quantified optical signal is much more complex than imaging alone would suggest. In brief, acute hippocampal slices were prepared with a chamber holding a submerged slice but with flow of artificial cerebrospinal fluid (aCSF) above and below, which we call interface-like. As soon as slices were placed in the chamber, aCSF with 0 Mg2+/5 K+ was used. Most mouse slices developed SD and did so in the first hour of 0 Mg2+/5 K+ aCSF exposure. In addition, prolonged bursts we call seizure-like events (SLEs) occurred, and the interactions between SD and SLEs suggest potentially important relationships. Differences between rats and mice in different chambers are described. Regarding optical imaging, SD originated in CA3 and the pattern of spread to CA1 and the dentate gyrus was similar in some ways to prior studies but also showed interesting differences. In summary, the methods are easy to use, provide new opportunities to study SD, new insights, and are inexpensive. They support previous suggestions that SD is diverse, and also suggest that participation by the dentate gyrus merits greater attention.